2008
DOI: 10.1111/j.1526-4637.2007.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Denervation of the Lumbar Zygapophysial Joints—Targeting the Best Practice

Abstract: We believe that the technique using "tunnel vision" with anatomically appropriate cannula placement and use of a large-bore, curved needle with a 10-mm active tip may improve the results of radiofrequency denervation of lumbar zygapophysial joints. Providing a detailed description of an anatomically accurate technique should be of value to those seeking to perform this procedure in a valid manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
137
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(150 citation statements)
references
References 15 publications
8
137
3
1
Order By: Relevance
“…According to results of several clinical trials, RF denervation of lumbar facet joints seems to be a very effective therapy with a success rate of 43-87% after 1 year [7,12,13]. Compared to those trials, 22% success rate of our study in 1 year after therapy is disappointing.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…According to results of several clinical trials, RF denervation of lumbar facet joints seems to be a very effective therapy with a success rate of 43-87% after 1 year [7,12,13]. Compared to those trials, 22% success rate of our study in 1 year after therapy is disappointing.…”
Section: Discussioncontrasting
confidence: 46%
“…The highest long-term success rate (87%) was achieved by a study which included only patients with a BDI \ 17 and without previous surgery [7]. In a more recent larger study, in which patients with previous surgery were excluded, the success rate decreased much faster within 1 year to 47% [12]. In this study, the influence of depression on the results was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Gofeld et al (14), only the patients with an appropriate response to comparative double diagnostic blocks were evaluated and 55 of the 174 patients (31.6%) experienced no benefit from the RF procedure, 119 patients (68.4%) had well to excellent pain relief lasting from 6 to 24 months. They concluded that proper patient selection and anatomically correct FJRFs provides strong short-term and moderate longterm pain relief.…”
Section: Civelek E Et Al: Facet Joint Injection and Radiofrequency Dmentioning
confidence: 99%
“…Interventional management of facet arthropathy is done through injection of local anaesthetic (with or without steroid) either within the joint (intra-articular injection) or on to the medial branches [26,31,[35][36][37][38][39][40]. Once diagnosis is confirmed, radiofrequency ablation (RFA) of medial nerves is done for long term effect.…”
Section: Interventional Management Of Facet Painmentioning
confidence: 99%